Barrett's Esophagus and Esophageal Adenocarcinoma: An example of Malignant Transformation consecutive to Inflammatory Response due to Hydrochloric Acid Exposure. Revision - Español, Español; Español, Español (Revista del Hospital Italiano de Buenos Aires, 2025)
Introduction: A brief review aimed at presenting current knowledge on the mechanisms of progression from metaplasia to anaplasia at the molecular level and their possible implications for the prevention, classification, and treatment of this condition, from a Translational Medicine perspective. It focuses on the genetic and epigenetic alterations and the inflammatory phenotype underlying the onset and development of Barrett’s esophagus (BE) resulting from exposure to gastric juice.Objectives: To review the molecular and chromosomal aspects involved in the multistep malignant transformation process that links the changes characteristic of BE with dysplasia and esophageal adenocarcinoma (EAC).Materials and methods: A literature review was conducted in PubMed and Google Scholar. Twenty English-language articles were analyzed, prioritizing publications from the last ten years, although classic foundational works were also included. The search encompassed both reviews and original articles.Conclusion: In gastroesophageal reflux disease (GERD), the backflow of hydrogen ions and gastric components induces chronic inflammation and oxidative stress, promoting epigenetic modifications, chromosomal aberrations, mutations in tumor suppressor genes and oncogenes, as well as apoptosis inhibition and local immunosuppression, which drive progression toward adenocarcinoma. BE represents a paradigmatic model of carcinogenesis induced by a known acidic stressor, allowing the integration of molecular and histological changes into a progressive continuum and providing key evidence on the relationship between chronic inflammation and cancer.
Keywords: gastroesophageal reflux disease; Barrett’s esophagus; inflammation; progression; epigenetics; mutation; esophageal adenocarcinoma